2018
DOI: 10.1007/s11162-018-9512-4
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Bologna Process on Graduation: New Evidence from Italy

Abstract: Between 2001 and 2005, higher education in Italy went through a considerable process of reform according to the Bologna Process. This paper evaluates the effects of this process on the academic performance of students. We estimate the difference in gradua-tion probability between students who switched from pre-reform university courses to post-reform courses and students who carried on their pre-reform academic career. To this end, we considered a sample of 25,866 undergraduate students enrolled 1 year before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…For example, Hahm and Kluve (2019) report effects between plus ten and 18 percentage points, dependent on the estimation method. Studies for Italy also point towards positive effects of the Bologna Process on the time until graduation and student retention (Bondonio and Berton, 2018;Chies et al, 2019). Bondonio and Berton (2018), for example, find large positive effects on the two-year retention rate (+30 percentage points) and on the probability of on-time graduation (+6-18 percentage points).…”
Section: Student Retention and Student Dropoutsmentioning
confidence: 99%
“…For example, Hahm and Kluve (2019) report effects between plus ten and 18 percentage points, dependent on the estimation method. Studies for Italy also point towards positive effects of the Bologna Process on the time until graduation and student retention (Bondonio and Berton, 2018;Chies et al, 2019). Bondonio and Berton (2018), for example, find large positive effects on the two-year retention rate (+30 percentage points) and on the probability of on-time graduation (+6-18 percentage points).…”
Section: Student Retention and Student Dropoutsmentioning
confidence: 99%
“…At the students' future careers in the labor market is promising, the treatment group's average final overall grade is significantly higher. In Italy, a study by Chies (2016) showed that younger students who chose the Bologna reform outperformed their peers in terms completion and employment opportunity. The findings indicated that the reform's effectiveness in increasing efficiency, competency and completion was highly confirmed among students.…”
Section: Background Of the Problemmentioning
confidence: 99%
“…Entre ellos, lo señalado por Blanden y Machin (2004) yBratti et al (2008) cuando indican que la posibilidad de graduarse de la educación superior aumenta considerablemente al contar con ingresos más altos. Desde un ángulo distinto, nuestros hallazgos también encuentran relación con los estudios de Zarifa (2012) yZarifa et al (2018) cuando muestra que los titulados de entornos socioeconómicos más bajos experimentan dificultades para completar sus estudios a tiempo, o con los estudiosChies et al (2019) y Triventi et al (2017 que, al analizar la implementación del proceso de Bolonia en Europa, establecen un aumento de las desigualdades de clase.…”
unclassified